PELUANG PENINGKATAN KERJASAMA INDONESIA-AMERIKA SERIKAT PASCA PERJANJIAN KEMITRAAN KOMPREHENSIF - Lisbet Lisbet (Jurnal Politica, 2011)
Bilateral relations between Indonesia and The United State of America had been begun since the Indonesia’s Dependence. But, the relations had not always been connected. They even got worse when The Congress of The United State of America imposed an embargo to Indonesia related to the chaos in East Timor. After The Comprehensive Partnership Agreement in 2010, both parties were hoping that they will convince to make a better and also mutually beneficial future. Both parties have decided to develop the Comprehensive Partnership Agreement in order to enhance the relations especially in trade and security issues because both of the countries have the interdependence in both issues. Because of that, this paper will analyze about the importance of Indonesia to the United States of America and the beneficial to Indonesia after the Comprehensive Partnership Agreement.